Staphylococcus aureus virulence is enhanced by secreted factors that block innate immune defenses - Jongerius, I; Von Kockritz-Blickwede, M; Horsburgh, M; Ruyken, M; Nizet, V; Rooijakkers, S (2012)
Staphylococcus aureus is a leading human pathogen that causes a large variety of diseases. In vitro studies have shown that S. aureus secretes several small proteins that block specific elements of the host innate immune system, but their role in bacterial pathogenicity is unknown. For instance, the extracellular complement-binding protein (Ecb) impairs complement activation by binding to the C3d domain of C3. Its homolog, the extracellular fibrinogen-binding protein (Efb), is known to block both complement activation and neutrophil adhesion to fibrinogen. Here, we show that targeted inactivation of the genes encoding Ecb and Efb strongly attenuates S. aureus virulence in a murine infection model: mice experienced significantly higher mortality rates upon intravenous infection with wild-type bacteria (79%) than with an isogenic ΔEcbΔEfb mutant (21%). In addition, Ecb and Efb are both required for staphylococcal persistence in host tissues and abscess formation in the kidneys (27% for wild-type vs. 7% for the ΔEcbΔEfb mutant). During staphylococcal pneumonia, Ecb and Efb together promote bacterial survival in the lungs (p = 0.03) and block neutrophil influx into the lungs. Thus, Ecb and Efb are essential to S. aureus virulence in vivo and could be attractive targets in future vaccine development efforts. Copyright © 2012 S. Karger AG, Basel.